An Analysis of Politeness Strategies in the Directive Speech Acts in The Sleepover Movie - Ersi, Jannatul Firdaus; Ardi, Havid (English Language and Literature, 2024)
This research focuses on the main character's directed speech act and politeness methods in the movie The Sleepover (2020). The goals of this study are to discover what directed speech act utterances are utilized by the main character and what politeness tactics are used by the main character of the film. This study's data is an English script (subtitle) for The Sleepover Movie. The qualitative research method was applied in this study. The goal of this study is to discover what kind of directive speech act and politeness methods the main character use. The findings of this study concern three of four directed speech acts performed by the main character and four types of politeness methods employed by the character.